P-269 Embracing change: focusing on our people, our partnerships and our potential, arthur rank hospice charity: part 2 of our journey. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Webb, Liz
Abstract : Arthur Rank Hospice Charity is on a dual journey of moving from the NHS to independence and building and moving to a new hospice building. This presented us with a double dose of significant change for our staff in the space of 18 months. We recognised that we have an opportunity to shape and transform our organisational culture as a new team- a mixture 100 plus NHS staff and 20 previous charity staff. At the same time as embedding the NICE pathway-Workplace health policy and management practices (2015). Managing the changes taking place with our staff is vital to the ongoing success of the charity and quality of care that we provide. What we did: Pre TUPE of 100 NHS staff Charity CEO and NHS Clinical lead worked together to communicate clearly and robustly with both teams about what was happening and when. Occupational health support and 24/7 access to counselling. At point of integration of the two previous teams Effective communication. Programme of face to face meetings with the new senior leadership team: Communicated a new quality governance structure that supports information flow from bottom to top of the organisation. Commissioned a series of cultural workshops with all staff over 10 weeks. All staff were invited to the full day events and all attended except three. Outcomes of workshops and next steps Using a model of 'appreciative enquiry' the workshops identified where we were and what steps we needed to take to embed a culture of openness, transparency, innovation and change. A plan of work was developed to support the new culture and focus on wellbeing with the now integrated staff team. This includes Fortnightly bulletin Staff Forum clinical supervision for all clinical staff. 1.1 meetings with staff and line manager annual appraisal and clear objectives Research based journal club Closing the loop', ensuring information and outcomes from projects, investigations and complaints and shared with all. Move to new building-program of includes a team approach to resilience and change management.